Using the multi-bit feature of memristors for register files in signed-digit arithmetic units - Fey, Dietmar (Semiconductor Science and Technology, 2014)
One of the outstanding features of memristors is their principle possibility to store more than one binary value in a single memory cell. Due to their further benefits of non-volatility, fast access times, low energy consumption, compactness and compatibility with CMOS logic, memristors are excellent devices for storing register values nearby arithmetic units. In particular, the capability to store multi-bit values allows one to realise procedures for high-speed arithmetic circuits, which are not based on usual binary but on ternary values. Arithmetic units based on three-state number representation allow carrying out an addition in two steps, i.e., in O(1), independent of the operands word length n. They have been well-known in literature for a long time but have not been brought into practice because of the lack of appropriate devices to store more than two states in one elementary register or main memory cell. The disadvantage of this number representation is that a corresponding arithmetic unit would require a doubling of the memory capacity. Using memristors for the registers can avoid this drawback. Therefore, this paper presents a conceptual solution for a three-state adder based on tri-stable memristive devices. The principal feasibility of such a unit is demonstrated by SPICE simulations and the performance increase is evaluated in comparison with a ripple-carry and a carry-look-ahead adder.
UnivIS-Import:2015-03-11:Pub.2014.tech.IMMD.IMMD3.usingt_8
Keywords: memristors multi-bit storage; signed-digit arithmetic; ternary computer